An Exploratory Study of Ideal Medical Systems Based on the Experiences of Laypeople in South Korea - Soo-Young Yu; Eunyoung E. Suh; Seongmi Lim; Ji-yeon Kim (SAGE Open)
Due to a worldwide paradigm shift from a medical-centered system to patient-centered care, there is a need to recognize actual (practical) medical service from laypeople. In South Korea, intrinsic healthcare use characteristics such as the “Herd Behavior” have led to waiting many hours for a short treatment time at metropolitan-based major hospitals. Illustrating individual perceptions of an ideal healthcare system should take precedence when defining this issue. This study aimed to explore and describe laypeople in South Korea’s perceptions of ideal healthcare services based on their utilization of medical services. This qualitative study was conducted with 13 members of the National Participation Committee using semi-structured interviews. Qualitative data were analyzed using the thematic analysis method and visualized through a word cloud generated with MAXQDA software. Six themes were derived from the visualized words and an incremental analysis to explore perceptions of desirable medical services. Participants struggled to find a suitable hospital without expert guidance and felt objectified for their money. They distrusted and didn’t want to speak in front of medical professionals. They wanted their essential needs to be met regardless of their economic status. This study provides a description portrait of laypeople’s experiences related to healthcare services in South Korea, where medical services are predominantly provided by private hospitals with public insurance coverage. Users’ desire for tailored information through an integrated medical system that has a strong emphasis on people-centeredness must be embraced.